Fodbold som velfærd 1934 -1995: Mellem moralsk opbyggelighed og forretning - Olsen, David Holt (Forum for Idræt, 2011)
Artiklen belyser med afsæt i Joanne Martins organisationsteori velfærdssamfundet som en kulturelt og moralsk projekt i forhold til fodboldbevægelsen. In 1995 a rather unnoticed revolution occurred in Danish football. The future famous Danish football agent Karsten Aabrink agreed to make investments in the newly established football club FC Copenhagen provided that decisive changes regarding the division of stakes took place. His requirement was that the share of 50% which each of the founding clubs, B1903 and Københavns Boldklub, held, was reduced to 30% whereby they would lose their deciding holdings. As a consequence, businessmen were now able to work more unrestrained than previously. The article argues that the reason why this could happen in 1995 without any noticeable objection was not rooted in economic explanations, but rather had to do with the cultural factors expressed in the narratives of amateur gentleman football that evolved around the football movement from the 1930s and onwards. Furthermore, the article argues that the entire football movement was embedded in a political consensus on the macro level regarding the construction of the welfare state and thereby creating path dependence, which made it very difficult to implement professional football.